Caracterizacion pomologica de variedades y clones de albaricoque - Badenes, M.L.=700 1 Llacer, G.; Asins, M.J.; Guerri, J.
(En, Es)
ilus., 15 ref.
Keywords: PRUNUS ARMENIACA; ALBARICOQUE; FITOMEJORAMIENTO; CLONES; ESPAÑA; CARACTERIZACION